Complex Gastrointestinal and Endocrine Sources of Inflammation in Schizophrenia - Severance, Emily G.; Dickerson, Faith; Yolken, Robert H. (Frontiers in Psychiatry, 2020)
A low level, inflammatory phenotype is prevalent in individuals with schizophrenia but the source of this inflammation is not known. Studies of the gut-brain axis indicate that this inflammation may be related to the translocation of intestinal microbes across a permeabilized gut-vasculature barrier. In addition, studies of the endocrine system support that this inflammation may derive from effects of stress hormones and metabolic imbalances. Gastrointestinal (GI) and endocrine conditions are not mutually exclusive, but rather may have additive effects to produce this inflammatory phenotype in schizophrenia. Here, we examined a series of plasma biomarkers used to measure general inflammation and presumably microbial, gut-derived inflammation in 409 individuals with schizophrenia: c-reactive protein (CRP), lipopolysaccharide-binding protein (LBP), soluble CD14 (sCD14), and IgG antibodies to S. cerevisiae, bovine milk casein and wheat gluten. Individuals were stratified according to whether or not they had a comorbid GI or endocrine condition, both, or neither. In multivariate regression models, the presence of GI and endocrine conditions were additive for the GI-based marker, LBP, with significant associations only when both conditions were present compared to when both conditions were absent (OR=2.32, 95th% CI 1.05-5.13, p<0.03). In contrast, the marker of general inflammation, CRP, was strongly associated with primarily endocrine conditions (OR=3.64, 95th% CI 1.35-9.84, p<0.05). Overall associations were largely driven by the GI condition, gastroesophageal reflux disease (GERD), and by the endocrine condition, obesity. In univariate comparisons, S. cerevisiae IgG levels were significantly elevated only in persons with GI conditions (p<0.02), whereas antibodies to the food antigens were elevated in the presence of either or both conditions (p<0.005-0.04). More severe psychiatric symptoms were associated only with GI conditions (p<0.01-0.04). In conclusion, both GI and endocrine abnormalities may contribute to inflammation in schizophrenia, sometimes independently and sometimes as part of interactions which may represent complex integrated pathways. The accumulating evidence for multi-system inflammation in schizophrenia may lead to the development of new strategies to prevent and treat this devastating disorder.